Validitas and Reliabilitas - Muhammad Fakhri Ramadhan; Rusydi A. Siroj; Muhammad Win Afgani (Journal on Education, 2024)
An instrument is a tool that is used as a tool to measure a measuring object or collect data from a variable. An instrument is said to be good if it is valid and reliable. Validity consists of content, construct, empirical validity. The internal validity of dichotomous item scores and polytomous item scores respectively used biserial correlation and product moment correlation. The criteria for an item to be valid or invalid are based on the r-table value. Reliability of combined item consistency for dichotomous item scores and polytomous item scores respectively used KR-20 and Alpha coefficient. The interpretation of the reliability coefficient is a relative interpretation in the sense that there is no absolute limit that indicates what the minimum coefficient number must be achieved so that a measurement can be called reliable. However, the observed test scores provide information on the true scores of individual groups.